PENGARUH VARIASI JENIS CAIRAN PENUKAR PANAS TERHADAP KINERJA PEMANAS AIR TENAGA SURYA SISTEM PELAT DATAR YANG MENGGUNAKAN PRINSIP SIRKULASI PAKSA - Arifin, Zainul; Laksana, Dedi Dwi (ROTOR, 2013)
Solar water heater is a device that heats water using solar collectors as heat sink of radiation heat, which is forwarded to the pipe containing the fluid heat exchanger (heat exchanger). In this study, conducted comparative testing of solar water heating performance between the performance of the water heater that uses liquid water heat exchanger, airgaram 3.5%, and palm oil. Data collection was performed by taking the data every 30 minutes for 3 hours is at 9:00 to 12:00 pm and the test done 3 times on different days with variations in the type of fluid heat exchanger. From the study data taken include temperature liquid heat exchanger in and out the collector, and the water temperature in the tank, which is then carried out data processing to determine the mass flow rate, density of the fluid, temperature differences in the liquid heat exchanger incoming and outgoing collector (AT) , the performance of solar water heaters (q), and processing the data graphically. The results of the research of some kind of liquid water heat exchanger, brine 3.5%, and palm oil showed that liquid palm oil heat exchanger with a heat capacity of 1,866 kJ / kg. K and a boiling point of 175 0C is the greatest performance, the performance of the lowest value owned by the water. This is due to the value of palm oil heat capacity smaller than a heat capacity of water and greater than the capacity of brine 3.5%, but it is also influenced by the boiling point of palm oil is the highest of any other heat exchanger fluid.Â Key Words: Heat exchanger, heat capacity, performance, collector, boiling point.